(untitled) (Scientific journal of the Fergana State University, 2023)
The article examines the reforms in the field of interethnic relations in the Republic of Uzbekistan over the years of independence, the organizational and legal foundations of interethnic relations, as well as the role and importance of national and cultural centers in strengthening interethnic relations. The article argues that all this organizational work will contribute to the further development of interethnic relations